Pengaruh Pemberian Interferensi dan Ultrasound Pada Penerapan Hold RelaxTerhadap Perubahan Nyeri dan Jarak Gerak Sendi Lutut Pasien Osteoarthritis di RSUD Prof. HM. Anwar Makkatutu Bantaeng - Hendrik Hendrik; M. Nurdin T; Yonathan Ramba (Poltekkes Kemenkes Jakarta III, 2015)
Osteoarthritis is a degenerative disease that musculoskeletal disorders, where thenumber of events is likely to increase in line with increasing life expectancy of thepopulation.Physiotherapy is one of the most important factors in the treatment ofosteoarthritis in a comprehensive manner.This study purpose to compare a more effective method of interference and hold relaxwith ultrasound and hold relax to changes within the joint motion additional pain due toosteoarthritis of the knee joint. This study is experiment quasy by using pretest-posttest twogroup design. The study population was all patients with osteoarthritis who visited thePhysiotherapy Polyclinic Hospital Prof. HM. Anwar Makkatutu Bantaeng from January toApril 2015, amounting to 45 people. Samples were obtained by purposive sampling so thatthe sample size of 20 people were divided into two groups.The results showed differences in values actuality significant pain before and afteradministration of interference and hold relax with an average difference of 1.94 + 0.72 cmand a ROM of 16,500 + 5,800 with results Wilcoxon test p = 0.005 <α = 0:05.While theintervention ultrasound and hold relax obtained by the difference the average value of theactuality of pain 1:41 + 0:21 cm and ROM of 10.80 + 3.150 by Wilcoxon test results p =0.005 <α = 0:05.On the Mann-Whitney test obtained significant differences between the twotreatments, the average value of VAS with p = 0.029 <α = 0:05.While in the area of motionthere was no significant difference in the two groups on the value of ROM with p = 0.74> p= 0:05.It is concluded that there are changes in the actuality of pain and range of motion(ROM) before and after administration of hold interference and relax as well as ultrasoundand hold relax on the knee joint osteoarthritis patients.There is no difference in the distancechange of motion (ROM) between the two treatment groups.